2015
DOI: 10.1175/jas-d-14-0039.1
|View full text |Cite
|
Sign up to set email alerts
|

Decadal Relationship between European Blocking and the North Atlantic Oscillation during 1978–2011. Part I: Atlantic Conditions

Abstract: Both the positive and negative phases of the North Atlantic Oscillation (NAO+ and NAO−, respectively) and atmospheric blocking in the Euro-Atlantic sector reflect synoptic variability over the region and thus are intrinsically linked. This study examines their relationship from a decadal change perspective. Since the winter-mean NAO index is defined as a time average of instantaneous NAO indices over the whole winter, it is unclear how the activity of European blocking (EB) events can be related to the variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(67 citation statements)
references
References 70 publications
9
56
2
Order By: Relevance
“…1a). In addition, enhanced blocking is found from the Azores to Scandinavia as well as over Greenland, as many previous studies have shown (e.g., Scherrer et al 2006;Häkkinen et al 2011a;Luo et al 2015). The interannual standard deviation shows a very similar pattern and amplitude to those of the climatological mean ( Fig.…”
Section: A Winter Atmospheric Blocking Variabilitysupporting
confidence: 73%
“…1a). In addition, enhanced blocking is found from the Azores to Scandinavia as well as over Greenland, as many previous studies have shown (e.g., Scherrer et al 2006;Häkkinen et al 2011a;Luo et al 2015). The interannual standard deviation shows a very similar pattern and amplitude to those of the climatological mean ( Fig.…”
Section: A Winter Atmospheric Blocking Variabilitysupporting
confidence: 73%
“…Two other major regions of blocking occurrence are the Euro-Atlantic and Pacific sectors (Lejenäs and Økland, 1983;Tibaldi and Molteni, 1990). Euro-Atlantic blockings are closely related to the European precipitation (Trigo et al, 2004;Sousa et al, 2016), surface temperature (Trigo et al, 2004), and North Atlantic Oscillation (Luo et al, 2015a(Luo et al, , 2015b. Both Euro-Atlantic and Pacific blockings may influence the occurrence of sudden stratospheric warming (Nishii et al, 2009(Nishii et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The storm track activity indicates an eastward extension relative to its mean track position toward the northern British Isles (Figure d), consistent with increased winter precipitation and enhanced AR incidence there in recent decades [ Huntingford et al , , and references therein]. The eastward extension in the storm track might be associated with a shift in the NAO toward its positive phase during the period 1980–2000 and strengthened eastward (weakened westward) component of the North Atlantic storm track [ Luo et al , ]. These changes are in line with a northward shift in the jet stream, in agreement with the stronger zonal flow over the North Atlantic in a warmer climate with an intensified and less wobbly jet stream predicted by many climate models [e.g., Barnes and Polvani , ].…”
Section: Circulation Changes Across the North Atlantic Regionmentioning
confidence: 52%
“…Leading modes of variability, such as the NAO and AMO, often exert their impact on European winter climate through modulation of atmospheric blocking activity over the North Atlantic‐European sector [e.g., Scherrer et al , ; Croci‐Maspoli et al , ; Häkkinen et al , ; Davini et al , ; Luo et al , ]. Atmospheric blocking represents a prominent weather phenomenon in the extratropics: During a blocking situation, the large‐scale midlatitude zonal flow is impeded and meridional anomalies occur in the upper level jet; the anomalous circulation pattern remains largely stationary, generally persists for several days at a time, and is often associated with extreme events [e.g., Coumou and Rahmstorf , ].…”
Section: Introductionmentioning
confidence: 99%